Bolbaffroides dhofarensis (Coleoptera: Bolboceratidae), a new species from Oman - Král, David; Hillert, Oliver; Mencl, Ladislav; Sommer, David (Zootaxa, 2022)
Bolbaffroides dhofarensis Král, Hillert, Mencl & Sommer, new species, from Dhofar Governorate in south-western Oman is described. Relevant diagnostic characters (e.g., head and pronotum shape) of the new species and type material of two morphologically similar species, B. rollii (J. Müller, 1941) and B. validus (Klug, 1843) are photographically documented.